PENERAPAN STANDARD PELAYANAN MINIMAL (SPM) DALAM MENGUKUR KINERJA KEUANGAN DAERAH ( Kajian Tentang Penganggaran Daerah dengan Performance Budget System ) - Nugroho, Trilaksono (Profit: Jurnal Adminsitrasi Bisnis, 2008)
In general, related to budget planning, local government have to arrange APBD according to SPM that already obligated by central government. It consists of several success indicators and targets (indicator output, outcome, benefit and impact). It will be used for determining target of each program, calculating cost standard analysis and planning programming budgeting Keywords: New Public Management, Budgeting Reform, Performance, Budget System Traditional Budget, Zero-Base Budgeting, Planning Programming Budgeting